Clostridium septicum brain abscess. Issue 11 (21st November 2022) - Tan, Daryl Jian An; Sng, Edwin Chong Yu; Ling, Xi Wern
Abstract : We present a previously well woman in her 70s who was admitted for 2 weeks of progressively worsening abdominal pain, high fever and drowsiness. She was eventually diagnosed with Clostridium septicum brain abscess, meningoencephalitis and ventriculitis. The diagnosis was challenging as cerebrospinal fluid cultures were negative and a microbiological diagnosis was only obtained on brain biopsy. Despite early initiation of antibiotics that would have been effective against C. septicum, her central nervous system (CNS) infection progressed, and she eventually succumbed to the infection. Infections with C. septicum are typically fulminant and associated with high mortality. In a patient with a CNS infection and concomitant abdominal manifestations, infection with C. septicum should be considered.